PENGEMBANGAN LKPD DENGAN PENDEKATAN PMRI PADA MATERI OPERASI PERKALIAN ALJABAR MENGGUNAKAN KONTEKS COVID-19 - Ardi Yusuf Setiawan; Sujinal Arifin; Ambarsari Kusuma Wardani (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2022)
This study aims to produce a worksheet with the PMRI approach on algebraic multiplication operations material using the context of covid 19 which is valid, practical, and effective. This type of research is research and development from Tessmer which focuses on two stages, namely the preliminary stage and the formative evaluation stage which consists of the expert review, one-to-one evaluation, small group, and field test stages. The subjects of this research were class VII students of SMP Negeri 35 Palembang. Data collection techniques used are interviews, questionnaires and tests. From the results of the study, the following conclusions were obtained: (1) The validity of Student Worksheets can be shown bythe validation results with the validators at the expert review stage with an average score result of 3,65 by three validators. (2) The practicality of Student Worksheets can be shown by the results of the student questionnaire at the one-to-one evaluation stage with an average practicality level of 3.56, the small group stage with an average practicality level of 3.47, and the field test stage with an average practicality level of 3.58. (3) The effectiveness of student worksheets can be shown by student learning outcomes in the form of post tests in the small group stage with an average level of effectiveness of 79.33 and also in the field test stage with an average level of effectiveness of 86.93.